荒漠化地区县级潜在土地利用冲突识别 - Li, Qiao; Wu, Xiuqin; Wang, Manman (Beijing da xue xue bao, 2018)
In order to alleviate land use conflict and manage land efficiently, the authors select the typical area of Yanchi County of Ningxia Province as a case, use the LUCIS conflict identification model based on TM data and social economic data, and build a land use tendency evaluation system of construction, agricultural and ecological land. By means of the conflict discrimination matrix, the potential land use conflict types are recognized and potential land use conflict zone in Yanchi County can be divided into 4 types, including dominant area, weak conflict area, moderate conflict area and intense conflict area. Then it is divided into 12 types of conflict zone according to the combination of land use tendency. The result show that 58.90% of the total area faces a risk of potential land use conflict, mostly of moderate conflict, and mainly for the conflict between construction and agricultural land, agricultural and ecological land and conflict among the three types of land use; 6.82% of the total area faces a